2014
DOI: 10.1177/1420326x14559855
|View full text |Cite
|
Sign up to set email alerts
|

Assessment on acoustical performance of green office buildings in Malaysia

Abstract: Green building rating system outlines many requirements to be considered in order for a building to be certified as one. However, the rating tools failed at truly addressing the acoustical aspect which in turn deteriorates the acoustical quality in green buildings. As preliminary stage of this study, the objective is to assess the acoustical performance of three green office buildings in Malaysia in comparison to selected standard acceptability criteria. Four spaces containing meeting rooms and open-plan offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…One of the key elements deciding the reverberation period in acoustics is the volume, shape, and size of space (Long, 2014). The reverberation time in a large volume of spaces will be longer, resulting in poor speech intelligibility (Jalil et al, 2016). When a sound source is applied in a room, sound waves can propagate from the source of sound until they hit the room's boundary.…”
Section: Fundamental Of Atrium Shape and Relationship With Soundmentioning
confidence: 99%
“…One of the key elements deciding the reverberation period in acoustics is the volume, shape, and size of space (Long, 2014). The reverberation time in a large volume of spaces will be longer, resulting in poor speech intelligibility (Jalil et al, 2016). When a sound source is applied in a room, sound waves can propagate from the source of sound until they hit the room's boundary.…”
Section: Fundamental Of Atrium Shape and Relationship With Soundmentioning
confidence: 99%
“…In the study by Kaarlela-Tuomaala et al 15 and Abd Jalil et al, 16 open-plan offices were shown not suitable for professional workers because of the vulnerability to disturbance and unwanted noise, and for other types of workers to intervene accordingly. Several studies [17][18][19] indicated that improving indoor lighting and illumination conditions can improve users' visual comfort and reduce the annoyance ratio.…”
Section: Introductionmentioning
confidence: 97%